If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Z + -2 + -3y = 2x Reorder the terms: -2 + Z + -3y = 2x Solving -2 + Z + -3y = 2x Solving for variable 'Z'. Move all terms containing Z to the left, all other terms to the right. Add '2' to each side of the equation. -2 + Z + 2 + -3y = 2 + 2x Reorder the terms: -2 + 2 + Z + -3y = 2 + 2x Combine like terms: -2 + 2 = 0 0 + Z + -3y = 2 + 2x Z + -3y = 2 + 2x Add '3y' to each side of the equation. Z + -3y + 3y = 2 + 2x + 3y Combine like terms: -3y + 3y = 0 Z + 0 = 2 + 2x + 3y Z = 2 + 2x + 3y Simplifying Z = 2 + 2x + 3y
| 6x-18=5x+15 | | h-49=13.8 | | 3x-1=7-3y+2 | | 16+144t+324t^2=0 | | 3(x-20)-4(x+4)=-2(x-6) | | 4c(a-6)+7(a-6)= | | X+2x=1050 | | -6(-1)-2y=12 | | 8c-7c=16 | | 2x+6(1+5x)=230 | | (2x-7/4)=0 | | 25=k/5;k=5 | | x-3+2x=33 | | 8-5x=42 | | -2(3-5k)=-76 | | -5p-3(-p)-p=4 | | -7(x-7)=-84 | | .13x+14.95=.39x-15.00 | | Lg(3x-5)=-3 | | -5(3-7x)=-85 | | 4(-3m+2)=32 | | 40=32t | | 2n+8n-13=17 | | 1=w/6 | | (2v*3*4v)^4/2v^4 | | .39x-15.00=50 | | 5x-45=90 | | 5tanx+3=13 | | -4x+4=-4-4 | | 2m^2=784 | | -2=v/3 | | 11x-2x+68=11x+40 |